Antioxidant and Cytotoxic Activities of Methanolic Extracts from Mimusops elengi Flowers - Natungnuy, K.; Poeaim, S. (International Journal of Agricultural Technology, 2018)
The total phenolic content, antioxidant and cytotoxic activities of methanolic extracts from the petals and sepals of Mimusops elengi flowers were examined. The total phenolic content of methanolic extracts from petals and sepals using Folin-Ciocalteu method showed 49.32±3.04 and 93.36±3.58 mgGAE /g extract, respectively. The methanolic extract from sepals showed higher antioxidant activity than petals with IC50 (50% inhibitory concentration) values in DPPH and ABTS radical scavenging assay of 98.20 and 236.13 µg/ml, respectively. In addition, Fe3+-TPTZ reduction in FRAP method was 63.11 mgAAE /g extract. Furthermore, MTT assay was applied to evaluate cytotoxic activity against eight cell lines. The sepals extract exhibited high cytotoxic activity against six cancerous cell lines: TK6, HeLa, HepG2, HT-29, MCF-7 and KB with CC50 (50% cytotoxic concentration) values of 179.38, 379.06, 442.61, 500.66, 517.98 and 541.06 µg/ml, respectively. Nevertheless, the sepals extract exhibited cytotoxic activity against normal cell lines (L929 and Vero) with CC50 of 493.96 and 413.69 µg/ml. The results suggested that methanolic extract from sepals of M. elengi flowers revealed high antioxidant and cytotoxic activities. Further studies are needed to evaluate the constituent of bioactive compounds that beneficial for medicinal and cosmetic applications.